(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Once told that the legendary filmmaker Satyajit Ray in shooting for his movie removed the name boards of specific Bengali shop in the backdrops because he thought that the brands or product display might distract the audience. However, things have changed in due course of time, where the brands placed in the frames, shots, scenes, and even in the film title cards and film song lyrics, where the brands get much visibility. Product or Brand placement is a basic adverting format presented through various media to attract the audience. Today, the Product or Brand placement is popularly known as in-film advertising has become an integral part of the film industry. In the Indian context, the Product or Brand placement in film is one of the most important marketing strategies that advertisers follow. This article analyzes and evaluates various Product or Brand placement strategies implemented for promotional purposes in Tamil films by selecting the films based on its popularity and box-office success. This article also discusses the influence and impact of Product or Brand placement in the Tamil film industry.